Low-drift, high-stable ionic gel thin film, pressure sensor and preparation method and application thereof

CN122898080APending Publication Date: 2026-10-13WUTONG SENSATION CONTROL (BEIJING) TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611400374.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0007]本发明提供了一种低漂移、高稳定的离子凝胶薄膜、压力传感器及其制备方法和应用,至少解决了现有技术离子凝胶薄膜因分子链滑移导致的抗蠕变性能差、信号漂移严重,以及微观缺陷引发的离子泄漏和回弹性下降的问题,本发明有效兼顾了柔性压力传感器的高灵敏度与长期服役稳定性

Benefits of technology

本发明通过在离子液体中引入碳纳米管,利用离子液体与碳纳米管之间的π-π共轭作用和静电吸附作用,形成非共价修饰的CNT@IL结构。该结构显著改善了碳纳米管在聚偏氟乙烯基体中的分散性,避免了填料团聚。同时,离子液体作为界面桥接剂,在碳纳米管与聚偏氟乙烯基体之间构建相互作用,提升了界面结合强度。此外,本发明通过对聚偏氟乙烯聚合物进行高能辐照交联,使其从二维线型结构转变为三维交联网络结构。该三维网络有效限制了聚合物分子链在持续电场或外力作用下的滑移与松弛,大幅提升了材料的模量和抗蠕变性能,解决了离子凝胶薄膜因分子链滑移导致的信号时域漂移问题,并将碳纳米管与离子液体牢固锚定在基体中,有效防止了微观缺陷引发的离子泄漏,保障了传感器的长期服役稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898080A_ABST
    Figure CN122898080A_ABST
Patent Text Reader

Abstract

The application discloses a low-drift and high-stability ionic gel film, a pressure sensor and a preparation method and application thereof, and belongs to the technical field of flexible pressure sensors.The film raw materials comprise polyvinylidene fluoride polymer, ionic liquid, carbon nanotubes, nano filler, crosslinking agent and solvent; the carbon nanotubes are coated with ionic liquid to form a non-covalent modified CNT@IL structure; the polyvinylidene fluoride polymer is crosslinked by irradiation of the crosslinking agent to form a three-dimensional crosslinked network structure; and the intensity of the alpha crystal form characteristic peak in the infrared spectrum of the film is lower than that of the beta crystal form characteristic peak.The synergistic effect of the CNT@IL interface anchoring and the three-dimensional crosslinked network effectively inhibits the molecular chain slipping and ion leakage, significantly reduces the signal drift and mechanical hysteresis of the sensor, and balances the high sensitivity and long-term service stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ion gel film technology, specifically relating to a low-drift, highly stable ion gel film, a pressure sensor, its preparation method, and its application. Background Technology

[0002] In recent years, with the increasing portability of health monitoring equipment and the diversification of sensor applications, flexible pressure sensors have been widely used as an important information acquisition device. Flexible pressure sensors can be applied to any surface to measure force information, sense the properties of the target object, and convert the received information into an electrical signal output. Existing pressure sensors can be classified into piezoresistive, capacitive, piezoelectric, and triboelectric types based on their sensing mechanisms. Among them, ionized pressure sensors, using ionic liquids as the core sensing material, form an electric double layer when the electrode and the ion conductor are in contact, generating a large capacitance per unit area at the interface. This significantly improves the sensor's sensitivity compared to traditional capacitive pressure sensors and offers advantages such as high resolution, high signal-to-noise ratio, anti-interference, and static response. They are widely used in health monitoring, wearable electronic devices, human-computer interaction, and soft robotics.

[0003] Currently, the core functional layer of ionogel pressure sensors, the ionogel film, is mostly prepared by homogenizing thermoplastic polymers with ionic liquids. However, the plasticizing effect of ionic liquids reduces the hardness of the polymer, enhances the mobility of molecular chain segments, and decreases creep resistance. Its inherent viscoelasticity leads to time-varying deformation under continuous loads, causing time-domain drift in the sensing signal and significantly reducing the accuracy and reliability of the sensor. Furthermore, when subjected to a continuous electric field or external force, the linear molecular chains within the ionogel film slowly slip, resulting in minute deformations and the formation of microcracks or pores within or on the surface of the dielectric. These microcracks and non-uniform structural defects gradually expand into ion leakage channels, leading to ion leakage within the dielectric. Leakage not only affects the stability of the sensor but also causes signal drift, reduced sensitivity, and even device failure.

[0004] To address these issues, some existing technologies attempt to add conductive fillers such as carbon nanotubes or graphene to the dielectric layer to improve the material's electrical properties. However, this significantly increases the film modulus, compromising the material's flexibility. Furthermore, when subjected to a continuous electric field or external force, the dielectric material tends to adhere too tightly to the electrodes, reducing the sensor's resilience and limiting its lifespan.

[0005] Therefore, effectively improving the modulus and creep resistance of ionogel films, while preventing ionic liquid leakage and maintaining the resilience of the material, is crucial for reducing signal drift in ionized sensors. This is a technical problem that those skilled in the art urgently need to solve.

[0006] It should be noted that this part of the present invention only provides background technology related to the present invention, and does not necessarily constitute prior art or known technology. Summary of the Invention

[0007] This invention provides a low-drift, highly stable ion gel film, a pressure sensor, its preparation method, and its application. It at least solves the problems of poor creep resistance and severe signal drift caused by molecular chain slippage in existing ion gel films, as well as ion leakage and decreased resilience caused by microscopic defects. This invention effectively balances the high sensitivity and long-term service stability of flexible pressure sensors.

[0008] To achieve the above objectives, in a first aspect, the present invention provides a low-drift, highly stable ionogel film, comprising, by weight, 15-30 parts of polyvinylidene fluoride polymer, 10-20 parts of ionic liquid, 0.1-0.6 parts of carbon nanotubes, 0.1-5 parts of nanofiller, 0.1-0.6 parts of crosslinking agent, and 55-70 parts of solvent; the carbon nanotubes are coated with ionic liquid to form a non-covalently modified CNT@IL structure; the polyvinylidene fluoride polymer is crosslinked by irradiation through the crosslinking agent to form a three-dimensional crosslinked network structure; in the infrared spectrum of the ionogel film, 760-800 cm⁻¹... -1 The intensity of the characteristic peak of the α-crystal form of polyvinylidene fluoride at that location is below 830–850 cm⁻¹. -1 The intensity of the characteristic peak of the β-crystal form of polyvinylidene fluoride at that location.

[0009] Preferably, based on the total mass of the polyvinylidene fluoride polymer, the PVDF content in the polyvinylidene fluoride polymer is 80%~95%, and the PVDF-HFP content is 5%~20%; the weight-average molecular weight of PVDF is 900,000~1,100,000, and the molecular weight distribution is 1.8~2.2; the weight-average molecular weight of PVDF-HFP is 300,000~500,000, and the molecular weight distribution is 1.9~2.3.

[0010] Preferably, the ionic liquid is selected from at least one of 1-ethyl-3-methylimidazolium trifluoromethanesulfonylimide, 1-butyl-3-methylimidazolium di(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 3-methyl-1-hexylimidazolium bromide, and 1-ethyl-3-methylimidazolium acetate.

[0011] Preferably, the nanofiller is selected from at least one of α-alumina or γ-alumina.

[0012] Preferably, the crosslinking agent is selected from at least one of triallyl isocyanurate, triallyl cyanurate, or trimethylolpropane triacrylate.

[0013] Preferably, the solvent includes a first solvent and a second solvent; the first solvent is N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone, accounting for 80% to 95% of the total solvent mass; the second solvent is dimethyl carbonate, accounting for 5% to 20% of the total solvent mass.

[0014] Preferably, the infrared spectrum of the ionogel film further includes 701~705 cm⁻¹. -1 and 738~742 cm -1 The characteristic peak of SNS symmetric stretching vibration at 1330~1335 cm⁻¹ -1 and 1348~1352 cm -1 The characteristic peak of the -SO2 asymmetric contraction vibration at 1568~1572 cm⁻¹, and the characteristic peak of the -SO₂ contraction vibration at 1568~1572 cm⁻¹. -1 The characteristic peak of the stretching vibration of the imidazole ring skeleton at that location.

[0015] In a second aspect, the present invention provides a method for preparing an ion gel film according to the first aspect, comprising the following steps: Step S1: Add carbon nanotubes to a solvent, disperse them by ultrasonication, add ionic liquid and nanofiller, continue ultrasonication and mechanical stirring, so that the ionic liquid coats the surface of carbon nanotubes through non-covalent interaction to obtain CNT@IL dispersion. Step S2: Add the polyvinylidene fluoride polymer and crosslinking agent to the CNT@IL dispersion, heat and stir until completely dissolved to obtain an ionized solution; Step S3: Coat the ionized solution onto the substrate, heat to evaporate the solvent and dry to form a film, and then bake under vacuum to obtain the nascent ionogel film. Step S4: Under inert gas protection, the nascent ionogel film is subjected to high-energy irradiation treatment with an irradiation dose of 50~200kGy, an irradiation rate of 1~3 m / min, an irradiation distance of 10~20cm, and a nitrogen irradiation environment. Multiple irradiations with small doses are used, followed by annealing treatment to obtain the ionogel film.

[0016] Preferably, in step S1, the ultrasonic dispersion time is 30-60 min, the ultrasonication time is 10-30 min, and the mechanical stirring conditions are stirring at 30-50℃ for 2-4 h.

[0017] Preferably, in step S2, the polyvinylidene fluoride polymer includes PVDF and PVDF-HFP, and the heating and stirring conditions are 50~60°C for 12~24h.

[0018] Preferably, in step S3, the thickness of the wet film formed by coating is 100~2000μm; the conditions for drying the film by heating and evaporating the solvent are 70~85℃ for 20~26h; and the conditions for vacuum baking are 70~80℃ for 46~50h.

[0019] Preferably, in step S4, the irradiation source for the high-energy irradiation treatment is an electron beam or gamma rays; the annealing treatment conditions are 90~110℃ for 1~2 hours.

[0020] Thirdly, the present invention provides a pressure sensor comprising a backing substrate, an ion gel film, and interdigitated electrodes arranged in sequence.

[0021] Fourthly, the present invention provides an application of a pressure sensor in flexible electronic skin, wearable medical devices, human-computer interaction, or soft robots.

[0022] The beneficial effects of this invention are as follows: This invention introduces carbon nanotubes into an ionic liquid, utilizing the π-π conjugation and electrostatic adsorption between the ionic liquid and the carbon nanotubes to form a non-covalently modified CNT@IL structure. This structure significantly improves the dispersibility of carbon nanotubes in polyvinylidene fluoride (PVDF) matrix, preventing filler agglomeration. Simultaneously, the ionic liquid acts as an interfacial bridge, building interactions between the carbon nanotubes and PVDF matrix, enhancing interfacial bonding strength. Furthermore, this invention transforms the PVDF polymer from a two-dimensional linear structure to a three-dimensional cross-linked network structure through high-energy irradiation cross-linking. This three-dimensional network effectively restricts the slippage and relaxation of polymer molecular chains under continuous electric fields or external forces, significantly improving the material's modulus and creep resistance. It solves the signal time-domain drift problem caused by molecular chain slippage in ion gel films and firmly anchors the carbon nanotubes and ionic liquid in the matrix, effectively preventing ion leakage caused by microscopic defects and ensuring the long-term stability of the sensor.

[0023] The high-energy irradiation treatment of this invention constructs a three-dimensional cross-linked network. The introduction of cross-linking points restricts the conformational freedom of the molecular chains, causing the chain segments to tend to arrange in a planar zigzag conformation of all-trans. Combined with the annealing treatment after irradiation, sufficient thermal energy is provided for the chain segment rearrangement, synergistically promoting the transformation of polyvinylidene fluoride from the nonpolar α phase to the highly polar β phase. Combined with the structural feature that the intensity of the β crystal form characteristic peak is higher than that of the α crystal form characteristic peak in the infrared spectrum, the dipole moment and polar interaction of the material are significantly enhanced, optimizing the dielectric properties of the system. At the same time, the introduced nano-alumina filler acts as a nucleating agent to further promote the β phase transformation. Its surface hydroxyl groups form a hydrogen bond network with the ionic liquid and polymer, reducing interfacial leakage current. The above synergistic effect enables the ion gel film to maintain low dielectric loss while possessing a high dielectric constant. Combined with the surface micro-nano structure formed by the evaporation of the dual solvent system, the effective contact area between the sensing layer and the interdigitated electrode is increased, thereby significantly improving the sensitivity and signal-to-noise ratio of the pressure sensor.

[0024] The preparation method of this invention employs multiple irradiations with low doses, avoiding excessive chain breakage and degradation of polymer molecules caused by a single high-dose irradiation, thus ensuring the uniformity and integrity of the crosslinked network. Combined with a specific annealing process, internal stress in the film is effectively eliminated, promoting further improvement of the crosslinked network. This process is mild and controllable, resulting in ionogel films with uniform thickness and stable structure, suitable for large-scale industrial production. The assembled pressure sensor exhibits excellent response repeatability and structural reliability under dynamic cyclic complex loads. Attached Figure Description

[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 The image shows the FTIR characterization of the ionogel film provided in Example 1 of this invention. Figure 2 The images shown are SEM images of the ion gel film provided in Example 1 of this invention at different magnifications, namely 500 nm, 1 μm, 5 μm, and 20 μm. Figure 3 Images showing the hysteresis performance test of a pressure sensor fabricated from an ion gel film according to Embodiment 1 of the present invention. Figure 4 The image shows the 1MPa creep performance test of the pressure sensor made of the ion gel film provided in Embodiment 1 of the present invention. Figure 5Images of a pressure sensor made of an ion gel film according to Embodiment 1 of the present invention, showing 1000 full-scale dynamic drift tests. Figure 6 A frontal view schematic diagram of a pressure sensor made of an ion gel film according to Embodiment 1 of the present invention; Figure 7 This is a top-view schematic diagram of a pressure sensor made from an ion gel film according to Embodiment 1 of the present invention. Detailed Implementation

[0027] In this invention, unless otherwise stated, directional terms such as "up," "down," "left," and "right" are generally understood in conjunction with the accompanying drawings and the directions shown in actual applications.

[0028] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.

[0029] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0030] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. The terms "optional" and "discretionary" mean that they may or may not be included (or may or may not be present).

[0031] In a first aspect, the present invention provides a low-drift, highly stable ion gel film, wherein the raw materials for preparation include, by weight, 15 to 30 parts of polyvinylidene fluoride polymer, which can be 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts and any value between them. The ionic liquid is 10 to 20 parts, which can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 parts and any value between them; The carbon nanotubes are 0.1 to 0.6 parts, and can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 parts, or any value between them; The nanofiller is 0.1 to 5 parts, and can be 0.1 parts, 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, and any value between them; The crosslinking agent is used in amounts of 0.1 to 0.6 parts, which can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 parts, or any value between them. The solvent is 55 to 70 parts, which can be 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70 parts and any value between them; Carbon nanotubes are coated with ionic liquids to form a non-covalently modified CNT@IL structure; polyvinylidene fluoride polymers are cross-linked by radiation through a cross-linking agent to form a three-dimensional cross-linked network structure. In the infrared spectrum of the ionogel film, 760~800 cm⁻¹ -1 The intensity of the characteristic peak of the α-crystal form of polyvinylidene fluoride at that location is below 830–850 cm⁻¹. -1 The intensity of the characteristic peak of the β-crystal form of polyvinylidene fluoride at that location.

[0032] Understandably, in response to the technical shortcomings of existing technologies, such as increased molecular chain mobility and decreased creep resistance of thermoplastic polymers under the plasticizing effect of ionic liquids, as well as signal drift caused by ion leakage due to microscopic defects, this invention provides a new solution by constructing a multi-scale collaborative micro-network structure and interface coupling mechanism.

[0033] Regarding the proportions of each component, if the polyvinylidene fluoride polymer content is too low, a continuous supporting framework cannot be formed, resulting in insufficient mechanical strength of the film; if the content is too high, the film will be too rigid and too inflexible. If the ionic liquid content is too low, it cannot provide sufficient ionic conductivity; if the content is too high, it will exacerbate the plasticizing effect and lead to creep deterioration. The controlled content of carbon nanotubes and crosslinking agents ensures the balance between the penetration threshold and crosslinking density of the conductive network, so that the conductive pathways constructed by carbon nanotubes and the mechanical network constructed by crosslinking agents can interpenetrate and synergize in space, ultimately endowing the ionogel film with excellent comprehensive properties of low drift, high stability, and high sensitivity.

[0034] Specifically, the non-covalently modified CNT@IL structure described in this invention refers to a composite structure formed by the π-π conjugation effect generated by the aromatic ring structure on the ionic liquid cation and the conjugated large π bonds on the sidewalls of the carbon nanotube, as well as the electrostatic adsorption and cation-π interaction between the ionic liquid cation and the carbon nanotube surface, resulting in the uniform and tight coating of ionic liquid molecules on the carbon nanotube surface. This process does not destroy the intrinsic sp of the carbon nanotube. 2 Hybrid carbon framework. This structure retains the excellent long-range conductivity and mechanical strength of carbon nanotubes while utilizing the long alkyl chains of the ionic liquid to provide steric hindrance, preventing van der Waals-driven aggregation of carbon nanotubes in the polymer matrix. Simultaneously, the ionic liquid coating the carbon nanotube surface acts as an interfacial bridger; its polar groups can generate strong dipole-dipole and charge-dipole interactions with the carbon-fluorine bonds in the polyvinylidene fluoride (PVDF) matrix. This creates multiple chemical and physical interfaces between the carbon nanotubes and PVDF, significantly improving interfacial bonding strength and load transfer efficiency.

[0035] Furthermore, the three-dimensional cross-linked network structure described in this invention refers to a cross-linked system with a spatial network topology formed when polyvinylidene fluoride (PVDF) polymer molecular chains undergo dehydrogenation reactions under high-energy irradiation to generate macromolecular free radicals. These free radicals are then connected via carbon-carbon covalent bonds through the bridging effect of the multifunctional groups of the cross-linking agent. This three-dimensional network effectively restricts the slippage and relaxation of polymer molecular chains under continuous electric fields or external forces, significantly improving the material's storage modulus and creep resistance, and solving the problem of signal time-domain drift caused by molecular chain slippage in ionomer gel films. More importantly, this three-dimensional cross-linked network exhibits a significant synergistic effect with the aforementioned CNT@IL structure. The cross-linked network locks the carbon nanotubes coated with ionic liquid within the three-dimensional framework, effectively suppressing the displacement and aggregation of carbon nanotubes during pressure cycling, stabilizing the conductive network structure, and simultaneously cutting off ion leakage channels formed by the propagation of microcracks in the matrix, effectively preventing ion leakage caused by microscopic defects.

[0036] Regarding infrared spectral characteristics, polyvinylidene fluoride (PVDF) exists in several crystalline forms. The α-form is a thermodynamically stable, nonpolar crystalline form where the dipole moments of the molecular chains cancel each other out. The β-form, however, is an all-trans planar zigzag conformation, exhibiting extremely high spontaneous polarizability and dielectric properties. In the infrared spectrum, the 760–800 cm⁻¹... -1 The characteristic peaks within the range are attributed to the bending vibrations of the CF2 group in the α crystal form, while those in the 830–850 cm⁻¹ range... -1The characteristic peaks within the range are attributed to the symmetric stretching vibrations of the CF2 and CH2 groups in the β-phase. The intensity of the characteristic peaks in the α-phase is lower than that in the β-phase in the infrared spectrum, macroscopically indicating that polyvinylidene fluoride (PVDF) is dominated by the highly polar β-phase. The mechanism of this crystal transformation may include, but is not limited to, the following explanations: high-energy irradiation crosslinking constructs covalent bond points between molecular chains, restricting the random motion of chain segments and making the molecular chains more inclined to adopt an all-trans planar zigzag conformation during crystallization; simultaneously, the dipole interaction between the hydroxyl groups on the surface of the nano-alumina filler and the CF2 groups on the PVDF segments provides heterogeneous nucleation sites, further promoting the preferential nucleation and growth of the β-phase; the annealing treatment after irradiation provides the thermodynamic driving force for the rearrangement of chain segments and crystal form perfection. The synergistic effect of these factors results in a significantly higher β-phase content in the final film compared to the α-phase. This crystal transformation significantly enhances the dipole moment and polar interaction within the material, not only optimizing the dielectric properties of the system and further strengthening the binding ability of polyvinylidene fluoride to ionic liquids, reducing interfacial leakage current, but also providing a higher intrinsic capacitance change rate for the pressure sensor, thereby greatly improving the sensor's sensitivity and signal-to-noise ratio.

[0037] Preferably, based on the total mass of the polyvinylidene fluoride polymer, the PVDF content in the polyvinylidene fluoride polymer is 80%~95%, and can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, or any value between them; the weight-average molecular weight of PVDF is 900,000~1,100,000, and can be 9,000. 00, 920000, 940000, 960000, 980000, 1000000, 1020000, 1040000, 1060000, 1080000, 1100000 and any value between them; the molecular weight distribution is 1.8~2.2, and can be 1.8, 1.85, 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2 and any value between them; The content of PVDF-HFP is 5%~20%, and can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or any value between them; the weight-average molecular weight of PVDF-HFP is 300,000~500,000, and can be 300,000, 310,000, 320,000, 330,000, 340,000, 350,000, 360,000, 370,000, 380,000, 390,000, 500,000, or any value between them; the molecular weight distribution is 1.9~2.3, and can be 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, or any value between them.

[0038] Understandably, the choice of a polyvinylidene fluoride (PVDF) and PVDF-hexafluoropropylene copolymer blend in the specific composition design of the polymer matrix aims to achieve a balance between mechanical toughness, creep resistance, and ion transport performance. PVDF, as the main component of the matrix, provides a stable polymer backbone for the entire ionogel network. Its molecular chains contain numerous strongly polar carbon-fluorine bonds, enabling coordination with ionic liquids through ion-dipole interactions, thus facilitating the uniform dispersion of the ionic liquids within the matrix. The selection of PVDF with a high weight-average molecular weight of 900,000–1,100,000 is to utilize the dense physical entanglement between the ultra-long molecular chains to impart excellent tear strength and fatigue fracture resistance to the film. Controlling the molecular weight distribution within the range of 1.8–2.2 avoids the low molecular weight fraction acting as an internal plasticizer, which could lead to unnecessary long-term creep in the material. The introduction of polyvinylidene fluoride (PVDF)-hexafluoropropylene (HFA) is to regulate the crystallinity of the matrix. The steric hindrance effect of the asymmetric groups of HFA disrupts the original regular chain segment arrangement of PVDF, reduces the crystalline region of the polymer, and increases the free volume of the amorphous region. The amorphous region is the main channel for ionic liquid storage and ion migration. Therefore, 5%–20% PVDF-HFA can significantly improve the response sensitivity and ionic conductivity of the ionization sensor. The weight-average molecular weight of this component is set at 300,000–500,000. Its relatively low molecular weight allows it to act as a flexible connecting bridge in the PVDF polymer chain network, improving the processing rheological properties of the blend system. At the same time, its molecular chain contains more active sites, making it easier to generate free radicals during irradiation crosslinking, improving crosslinking efficiency, and making the three-dimensional network structure more compact and complete.

[0039] Preferably, the ionic liquid is selected from at least one of 1-ethyl-3-methylimidazolium trifluoromethanesulfonylimide (EMIM-TFSI), 1-butyl-3-methylimidazolium di(trifluoromethanesulfonyl)imide (BMIM-TFSI), 1-butyl-3-methylimidazolium tetrafluoroborate (BMIM-BF4), 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM-PF6), 3-methyl-1-hexylimidazolium bromide ([HMIM]Br), and 1-ethyl-3-methylimidazolium acetate ([EMIM]Ac).

[0040] Preferably, the nanofiller is selected from at least one of α-alumina or γ-alumina.

[0041] Preferably, the crosslinking agent is selected from at least one of triallyl isocyanurate (TAIC), triallyl cyanurate (TAC), or trimethylolpropane triacrylate (TMPTA).

[0042] Understandably, ionic liquids, as conductive and sensitive components of flexible pressure sensing films, possess excellent ionic conductivity and good fluidity, ensuring good compatibility with polymer matrices. The preferred imidazole or pyridine ionic liquids of this invention exhibit strong π-π interactions between their aromatic ring structures on the cations and the conjugated structures on the sidewalls of carbon nanotubes, resulting in stable adsorption on the carbon nanotube surface. Their anions possess extremely strong hydrophobicity and chemical inertness, effectively reducing the film's tendency to adsorb environmental moisture and ensuring electrochemical stability. The introduction of nano-alumina fillers has multiple synergistic effects, especially γ-alumina, whose surface is rich in Lewis acid sites and hydroxyl groups, enabling strong dipole-dipole interactions with the CF2 groups on the PVDF molecular chain. This serves as a heterogeneous nucleation site, preferentially inducing the nucleation and growth of the all-trans conformation β-crystal form. α-alumina primarily plays a role in rigidity enhancement and physical nucleation, improving the film's modulus and dimensional stability. Both can promote the crystallization of polyvinylidene fluoride (PVDF), enhancing the polarity and dielectric properties of the film. Simultaneously, their high specific surface area and surface hydroxyl groups can form multiple hydrogen bonds and dipole interactions with the polar groups of ionic liquids and the carbon-fluorine bonds of PVDF, further optimizing interfacial compatibility and reducing interfacial leakage current. The choice of crosslinking agent helps construct a stable three-dimensional network. Triallyl isocyanurate, triallyl cyanurate, or trimethylolpropane triacrylate are all multifunctional substances that can simultaneously connect multiple polymer chains to form a three-dimensional network bridge. Furthermore, these three types of substances have highly reactive double bonds, rapidly capturing irradiated polymer free radicals and participating in crosslinking, preventing polymer free radical chain breakage and degradation, significantly improving crosslinking efficiency while inhibiting material degradation. Moreover, they are not dependent on high temperatures, reacting efficiently under room-temperature electron beam irradiation, making them friendly to heat-sensitive materials.

[0043] Preferably, the solvent includes a first solvent and a second solvent; the first solvent is N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc) or N-methylpyrrolidone (NMP), accounting for 80% to 95% of the total mass of the solvent, and can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95% and any value between them; The second solvent is dimethyl carbonate (DMC), accounting for 5% to 20% of the total solvent mass, and can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% and any value between them.

[0044] Understandably, the preferred dual-solvent system of this invention facilitates efficient dissolution of each component and induces the formation of key surface microstructures during subsequent film formation. The first solvent, a strongly polar aprotic solvent, dominates the process; its high boiling point and excellent dissolving power break the crystalline entanglement between polyvinylidene fluoride (PVDF) molecular chains, ensuring a homogeneous and stable solution in the initial stages of preparation. The second solvent, dimethyl carbonate, has a relatively low boiling point and a rapid evaporation rate. This combination of solvents with different boiling points induces a significant gradient evaporation effect during the coating, drying, and film formation stages. In the initial stage of film formation, the second solvent on the surface layer rapidly evaporates, causing a sharp increase in the local concentration of the polymer solution, leading to thermodynamic instability and phase transformation. This phase separation mechanism induced by non-equilibrium solvent evaporation, combined with the spontaneous crystallization behavior of PVDF, forms numerous micro- and nano-scale protrusions and a dense, porous microstructure on the film surface. When a small pressure is applied, the surface protrusion structure easily undergoes compressive deformation, significantly increasing the effective contact area with the electrode, thereby generating a huge capacitance change and endowing the sensor with extremely high pressure resolution and sensitivity.

[0045] Preferably, when the ionic liquid is selected from imidazole ionic liquids containing trifluoromethanesulfonylimide anions, the infrared spectrum of the ion gel film further includes 701-705 cm⁻¹. -1 and 738~742 cm -1 The characteristic peak of SNS symmetric stretching vibration at 1330~1335 cm⁻¹ -1 and 1348~1352 cm -1 The characteristic peak of the -SO2 asymmetric contraction vibration at 1568~1572 cm⁻¹, and the characteristic peak of the -SO₂ contraction vibration at 1568~1572 cm⁻¹. -1 The characteristic peak of the stretching vibration of the imidazole ring skeleton at that location.

[0046] Understandably, the aforementioned infrared spectral characteristic peaks verify the successful introduction and structural integrity of ionic liquids in the composite system at the microscopic molecular level. Specifically, 701–705 cm⁻¹-1 and 738~742 cm -1 The characteristic peak at 1330–1335 cm⁻¹ is attributed to the symmetric stretching vibration of the sulfur-nitrogen-sulfur bond in the ionic liquid anion. -1 and 1348~1352 cm -1 The characteristic peak at 1568–1572 cm⁻¹ is attributed to the asymmetric contraction vibration of the sulfonyl group in the anion, while the peak at 1568–1572 cm⁻¹ is attributed to the asymmetric contraction vibration of the sulfonyl group in the anion. -1 The characteristic peaks at these locations are attributed to the stretching vibrations of the imidazole ring skeleton in the cation. The clear presentation of these characteristic peaks indicates that the ionic liquid containing anions such as trifluoromethanesulfonylimide and imidazole cations has been successfully and uniformly dispersed in polyvinylidene fluoride (PVDF) matrix. The complete preservation of the ionic liquid's molecular structure helps maintain the macroscopic sensing performance of the film. The intact ionic liquid structure ensures its continuous and stable dissociation of free anions and cations in the amorphous region and three-dimensional cross-linked network of the polymer, providing the film with high and stable ionic conductivity. Furthermore, the structurally intact imidazole ring and polar groups such as sulfonyl groups can fully exert their core function as interfacial bridgers. The aromatic structure and cations on the imidazole ring can form a tight physical bond with the electron-rich carbon-fluorine bonds in the PVDF matrix through strong dipole-dipole interactions and charge-dipole interactions; simultaneously, sulfonyl groups can form a multiple hydrogen bond network with the hydroxyl groups on the surface of fillers such as nano-alumina. These multi-scale intermolecular interactions effectively enhance the interfacial compatibility and bonding strength between carbon nanotubes, nanofillers, and the organic polymer matrix, significantly reducing microscopic defects and leakage current paths at the interface. This synergistic effect enables the ionogel film to maintain excellent ion transport capabilities while possessing extremely high dielectric stability, thereby macroscopically endowing the sensor with extremely low mechanical hysteresis, excellent creep resistance, and resistance to signal drift under long-term dynamic loads.

[0047] In a second aspect, the present invention provides a method for preparing an ion gel film according to the first aspect, comprising the following steps: Step S1: Add carbon nanotubes to a solvent, disperse them by ultrasonication, add ionic liquid and nanofiller, continue ultrasonication and mechanical stirring, so that the ionic liquid coats the surface of carbon nanotubes through non-covalent interaction to obtain CNT@IL dispersion. Step S2: Add the polyvinylidene fluoride polymer and crosslinking agent to the CNT@IL dispersion, heat and stir until completely dissolved to obtain an ionized solution; Step S3: Coat the ionized solution onto the substrate, heat to evaporate the solvent and dry to form a film, and then bake under vacuum to obtain the nascent ionogel film. Step S4: Under inert gas protection, the nascent ionogel film is subjected to high-energy irradiation treatment with an irradiation dose of 50~200kGy, an irradiation rate of 1~3 m / min, an irradiation distance of 10~20cm, and a nitrogen irradiation environment. Multiple irradiations with small doses are used, followed by annealing treatment to obtain the ionogel film.

[0048] Understandably, the present invention provides a preferred preparation method that organically combines non-covalent surface modification, solution blending and high-energy irradiation crosslinking technology through specific process steps to ensure the consistency of the microstructure and macroscopic properties of the final ionogel film.

[0049] It is understood that this invention is not limited to the specific preparation process described above. Those skilled in the art should understand that any ionogel film ultimately prepared possessing the non-covalently modified CNT@IL structure, three-dimensional cross-linked network structure, and corresponding infrared spectral characteristics described in this invention, and effectively solving the technical problems of poor creep resistance, ion leakage, and signal drift in traditional ionogel films, falls under the substantive protection scope of this invention. Without departing from the core technical concept of this invention, those skilled in the art can obtain films with the same microstructure and macroscopic properties by adjusting process parameters, replacing conventional solvents, or changing the feeding sequence, etc. Therefore, any equivalent preparation method or conventional process evolution that can prepare an ionogel film conforming to the structural characteristics and performance requirements of this invention should be included within the protection scope of this invention.

[0050] Step S1 utilizes a combination of ultrasound and mechanical stirring to break up the aggregates of carbon nanotubes through cavitation and shear force, allowing the ionic liquid to fully adsorb onto their surface. Step S2, involving heating and stirring, ensures complete dissolution of the high-molecular-weight polymer and untangles its physical entanglements. Step S3, the coating and drying process, simultaneously removes the solvent and promotes the development of surface micro / nano structures. Step S4, the high-energy irradiation treatment, is the core process of this invention; inert gas protection prevents the polymer from degrading and oxidizing under high temperature and high-energy radiation. Under high-energy radiation, the polyvinylidene fluoride (PVDF) molecular chains undergo dehydrogenation and generate free radicals, which then recombine to form carbon-carbon covalent cross-links, constructing a stable three-dimensional network structure. Employing a low-dose, multiple-irradiation method (specifically, each irradiation dose can be 10-50 kGy, divided into 3-10 irradiations, with cooling to room temperature between adjacent irradiations) avoids localized heat accumulation and excessive chain breakage and degradation of the polymer molecular chains caused by a single high-dose irradiation, ensuring uniform growth of the cross-linked network. The annealing treatment after irradiation provides sufficient mobility to the molecular chain segments, promotes the further combination of residual free radicals, improves the three-dimensional cross-linking network and eliminates the internal stress inside the film, thereby endowing the film with excellent thermal stability, mechanical strength and creep resistance.

[0051] Preferably, in step S1, the ultrasonic dispersion time is 30-60 min, the ultrasonication time is 10-30 min, and the mechanical stirring conditions are stirring at 30-50℃ for 2-4 h.

[0052] Understandably, controlling the ultrasonication and stirring time and temperature in step S1 helps achieve uniform dispersion and non-covalent modification of carbon nanotubes. An initial ultrasonication time that is too short cannot effectively peel off the carbon nanotube bundles, while a time that is too long may damage the carbon nanotube structure. Controlling the duration of continued ultrasonication ensures that the ionic liquid and the carbon nanotube surface reach adsorption equilibrium, forming a stable coating layer. Temperature control during mechanical stirring aims to provide suitable thermal energy to promote the diffusion of ionic liquid molecules to the carbon nanotube surface, while avoiding excessive solvent evaporation or excessively high system temperatures that could lead to ionic liquid decomposition.

[0053] Preferably, in step S2, the polyvinylidene fluoride polymer includes PVDF and PVDF-HFP, and the heating and stirring conditions are 50~60°C for 12~24h.

[0054] Understandably, the temperature range of 50-60°C in step S2 provides sufficient heat to break the crystalline entanglement between the polyvinylidene fluoride molecular chains, allowing them to fully expand and solubilize, without causing thermal degradation of the polymer or premature decomposition of the crosslinking agent. A stirring time of 12-24 hours ensures the complete elimination of the concentration gradient within the system, resulting in a homogeneous and stable ionized solution, which contributes to the uniform development of the microstructure during subsequent film formation.

[0055] Preferably, in step S3, the thickness of the wet film formed by coating is 100~2000μm; the conditions for drying the film by heating and evaporating the solvent are 70~85℃ for 20~26h; and the conditions for vacuum baking are 70~80℃ for 46~50h.

[0056] Understandably, controlling the wet film thickness in step S3 affects the final film's microstructure development and solvent removal efficiency. Excessive thickness makes it difficult to completely remove the internal solvent, while insufficient thickness makes it difficult to form a complete surface micro / nano structure. Heating at 70-85°C causes the low-boiling-point co-solvent to evaporate preferentially, inducing the formation of surface micro / nano structures. Subsequent vacuum baking removes the high-boiling-point main solvent, preventing solvent residue from plasticizing the film and weakening its creep resistance.

[0057] Preferably, in step S4, the irradiation source for the high-energy irradiation treatment is an electron beam or gamma rays; the annealing treatment conditions are 90~110℃ for 1~2 hours.

[0058] Understandably, the temperature of 90~110℃ in step S4 is higher than the glass transition temperature of polyvinylidene fluoride but lower than its melting point. At this temperature, the polymer chain segments have sufficient mobility to promote the full combination of residual free radicals generated by irradiation, further improve the three-dimensional cross-linked network, and effectively release the internal stress accumulated during film formation and irradiation, thereby improving the dimensional stability and long-term service reliability of the film and ensuring the signal fidelity of the sensor under complex working conditions.

[0059] Thirdly, the present invention provides a pressure sensor comprising a backing substrate, an ion gel film, and interdigitated electrodes arranged in sequence.

[0060] Understandably, the pressure sensor provided in this application employs an asymmetric AB layered structure. The backing substrate, serving as the underlying support, is typically made of flexible insulating material, such as polyethylene terephthalate film or polyimide film. The main function of the backing substrate is to provide necessary macroscopic mechanical support for the internally ionically conductive sensitive layer, ensuring the integrity of the overall structure when subjected to bending, torsion, or shear stress, and preventing tearing or damage to the sensitive ion gel film. Interdigitated electrodes are disposed on the other side of the ion gel film, their alternating finger-like structures creating a symmetrical edge electric field. Under the influence of the electric field, the anions and cations within the ion gel film are directionally enriched at the electrode interface, forming a stable double-layer capacitance structure. The ion gel film of this application possesses extremely low mechanical hysteresis and creep resistance; its effective contact area with the interdigitated electrodes changes accurately and reversibly reflecting the magnitude of external pressure when under pressure. After the external load is unloaded, the film can quickly recover its initial microstructure without residual plastic deformation causing signal baseline drift. In addition, the tight bonding between the backing substrate and the ionogel film eliminates interfacial gaps, avoids additional parasitic capacitance introduced by the interfacial air layer, and ensures high fidelity and long-term reliability of the sensor's capacitive signal.

[0061] Preferably, the thickness of the backing substrate is controlled within the range of 10~300μm. Limiting the thickness of the backing substrate within this range ensures, on the one hand, that the substrate has sufficient mechanical strength and dimensional stability, preventing wrinkling or excessive stretching deformation of the film during assembly or actual attachment, thereby ensuring uniform transmission of external stress to the ionogel film; on the other hand, this thickness range allows the sensor to maintain excellent overall flexibility, enabling it to closely conform to human skin or various complex curved surfaces, avoiding stress shielding effects or signal distortion caused by poor adhesion due to excessive substrate thickness.

[0062] Fourthly, the present invention provides an application of a pressure sensor in flexible electronic skin, wearable medical devices, human-computer interaction, or soft robots.

[0063] Understandably, the pressure sensor provided by this invention exhibits significant technical advantages and high adaptability in the aforementioned cutting-edge application fields. In wearable medical device applications, the sensor needs to be closely attached to the human skin for extended periods, enduring static pre-tension forces caused by strap tension. For traditional gel sensors, this long-term static load leads to severe creep flow in the material, causing the gel thickness to gradually thin, resulting in continuous and uncontrollable drift of the sensor's baseline capacitance, directly causing distortion or even complete failure of physiological signal extraction. The ionogel film of this invention, benefiting from a three-dimensional cross-linked network and interface coupling mechanism, possesses excellent creep resistance and dimensional stability, ensuring long-term high stability of the reference signal under continuous external force, thus guaranteeing the reliability of medical-grade parameter monitoring. In flexible electronic skin and human-computer interaction scenarios, the sensor needs to respond instantaneously to high-frequency dynamic actions and maintain signal consistency during repeated cycles. The low hysteresis and high resilience of this sensor ensure zero-delay stress response and signal recovery, enabling rapid and accurate response to minute pressure changes. In the field of soft robotics, sensors need to adapt to large strain deformations on complex curved surfaces. The thin film of this invention has excellent flexibility and elongation at break, which can closely adhere to the surface of robot joints and accurately capture multi-dimensional tactile feedback information, meeting the application requirements for accurate and stable pressure feedback in complex working environments.

[0064] The present invention will be further described in detail below through specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.

[0065] Example 1 This embodiment provides a method for fabricating a low-drift, highly stable ion gel film and a pressure sensor thereof. The sensor includes interdigitated electrodes, an ion gel film, and a backing substrate arranged sequentially.

[0066] The raw materials of the ionogel film include the following components by weight: 13 parts PVDF, 2 parts PVDF-HFP, 10 parts ionic liquid EMIM-TFSI, 0.5 parts carbon nanotubes, 3 parts nano alumina, 0.2 parts crosslinking agent TAIC, 54 parts first solvent DMF, and 6 parts second solvent DMC.

[0067] The preparation method of the above-mentioned ionogel film includes the following steps: S1: Preparation of CNT@IL 0.5 parts of carbon nanotubes were added to a mixed solvent of DMF and DMC in a mass ratio of 54:6. The cells were lysed and ultrasonically dispersed for 30 to 60 minutes to obtain a uniform black suspension. 10 parts of ionic liquid EMIM-TFSI and 3 parts of nano-alumina were added, and the mixture was ultrasonically dispersed for another 10 to 30 minutes. The mixed solution was mechanically stirred at 30 to 50°C for 2 to 4 hours to allow the ionic liquid to fully coat the surface of the carbon nanotubes through π-π stacking and electrostatic interaction, thereby obtaining a stable CNT@IL dispersion.

[0068] S2: Preparation of ionized solution Dissolve 13 parts of PVDF and 2 parts of PVDF-HFP in the above mixed dispersion containing CNT@IL, and stir at 50 to 60°C for 12 to 24 hours to ensure complete dissolution of the polymer, to obtain an ionized solution.

[0069] S3: Electrostatic thin film coating The ionized solution was evenly coated onto a clean and smooth PET film with a thickness of 100 μm, which had been wiped with anhydrous ethanol, using a scraper. The film was then placed on a water platform in an oven and heated and dried at 70 to 85°C for 24 hours. After the solvent had completely evaporated and the film had formed, it was vacuum baked at 70 to 80°C for 48 hours and then stored for later use.

[0070] S4: Ionized thin film irradiation treatment Remove the dried PVDF film, cut it to a suitable size, and lay it flat on the irradiation sample holder, ensuring the film surface is smooth and wrinkle-free. Start the electron beam irradiator and set the irradiation parameters: irradiation dose 150 kGy, irradiation rate 2 m / min, irradiation distance 15 cm, and irradiation environment nitrogen. Place the sample holder into the irradiator and perform multiple irradiations with small doses. After completion, remove the sample to obtain the irradiated cross-linked PVDF film. Place the irradiated PVDF film in a vacuum oven and anneal it at 90 to 110°C for 1 to 2 hours to promote the improvement of the cross-linking network and eliminate internal stress in the film. After cooling to room temperature, it can be used for subsequent sensor assembly.

[0071] The assembly method of the above-mentioned ion gel film pressure sensor includes the following steps: using a ring-shaped double-sided adhesive to assemble the ion gel film with a 50μm thick PET backing substrate and the interdigitated electrodes face to face to form an AB structure sensor. The outer layer of the PET backing is encapsulated and protected with PI tape for subsequent application testing.

[0072] Example 2 The only difference between this embodiment and Embodiment 1 is that the amount of crosslinking agent and the dose of irradiation treatment have been adjusted.

[0073] The specific raw material ratio is as follows: 13 parts PVDF, 2 parts PVDF-HFP, 10 parts ionic liquid EMIM-TFSI, 0.5 parts carbon nanotubes, 3 parts nano alumina, 0.3 parts crosslinking agent TAIC, 54 parts first solvent DMF, and 6 parts second solvent DMC.

[0074] In step S4, the irradiation dose is set to 100 kGy, and the rest of the preparation method and sensor assembly method are the same as in Example 1.

[0075] Example 3 The only difference between this embodiment and Embodiment 1 is that the content of nano-alumina filler is increased.

[0076] The specific raw material ratio is as follows: 13 parts PVDF, 2 parts PVDF-HFP, 10 parts ionic liquid EMIM-TFSI, 0.5 parts carbon nanotubes, 5 parts nano alumina, 0.2 parts crosslinking agent TAIC, 54 parts first solvent DMF, and 6 parts second solvent DMC.

[0077] The preparation method and sensor assembly method are the same as those in Example 1.

[0078] Example 4 The only difference between this embodiment and Example 1 is that the type of crosslinking agent has been changed, and trimethylolpropane triacrylate (TMPTA) has been used instead of triallyl isocyanurate (TAIC).

[0079] The specific raw material ratio is as follows: 13 parts PVDF, 2 parts PVDF-HFP, 10 parts ionic liquid EMIM-TFSI, 0.5 parts carbon nanotubes, 3 parts nano alumina, 0.2 parts crosslinking agent TMPTA, 54 parts first solvent DMF, and 6 parts second solvent DMC.

[0080] The preparation method and sensor assembly method are the same as those in Example 1.

[0081] Comparative Example 1 The only difference between this comparative example and Example 1 is that carbon nanotubes are not added to the raw material formulation.

[0082] The specific raw material ratio is as follows: 13 parts PVDF, 2 parts PVDF-HFP, 10 parts ionic liquid EMIM-TFSI, 3 parts nano alumina, 0.2 parts crosslinking agent TAIC, 54 parts first solvent DMF, and 6 parts second solvent DMC.

[0083] The preparation method and sensor assembly method are the same as those in Example 1.

[0084] Comparative Example 2 The only difference between this comparative example and Example 1 is that the high-energy irradiation treatment in step S4 is not performed.

[0085] The specific raw material ratios are the same as in Example 1.

[0086] In its preparation method, step S4 is skipped, and the nascent film after vacuum baking in step S3 is directly used for sensor assembly. The remaining assembly methods are the same as in Example 1.

[0087] Test case The crosslinking density of the ionogel films prepared in Examples 1 to 4 and Comparative Examples 1 and 2 of this application was tested using the swelling method, and the hysteresis, 1MPa creep and 1000 full-scale dynamic drift performance of the encapsulated ionized pressure sensors were tested.

[0088] Gel content test method: Take the irradiated PVDF film, cut a 1cm×1cm sample, dry it at 105℃ for 2h to constant weight, and record the mass m1; put the sample into a Soxhlet extractor, use acetone as solvent, reflux extract for 24h to remove the soluble part; take out the sample, dry it at 105℃ to constant weight, and record the mass m2; calculate the gel content (%) = (m2 / m1)×100%, and take the average value of 3 parallel tests.

[0089] Hysteresis test method: Pressure is applied using a pressure source device. The test mode is stepped pressure application: 0MPa, 0.2MPa, 0.4MPa, 0.6MPa, 0.8MPa, 1MPa, 1MPa, 0.8MPa, 0.6MPa, 0.4MPa, 0.2MPa, 0MPa. Each step is tested for 30 seconds. This process constitutes one cycle, and three cycles are required. Force data and electrical signal data are collected during the test. Within the specified range, at the same test point, the percentage of hysteresis error is calculated using the absolute value of the difference between the output when the measured value increases and decreases.

[0090] 1MPa creep test method: A pressure source device is used to pressurize the device. The pressurization mode is to first collect the output under no pressure, and then apply a full-scale pressure of 1MPa after 1 minute. The pressure is held for 1 hour, and force data and electrical signal data are collected. The percentage of the maximum signal difference value to the initial full-scale output value is calculated during the entire test cycle.

[0091] 1000-cycle full-scale dynamic drift test method: Pressurization is applied using a pressure source device. The test mode is to start from zero pressure, apply continuous force to the expected range, and then continuously reduce the pressure from the expected range back to zero pressure. This process is one cycle, with a cycle period of 40 seconds. 1000 cycles need to be tested. Force data and electrical signal data are collected during the test. The percentage of the maximum difference in full-scale output value to the initial full-scale output value is calculated over the entire test cycle.

[0092] Test Results The test data for each embodiment and comparative example are shown in Table 1.

[0093] Table 1

[0094] As shown in Table 1, Example 1 introduced ionic liquid and carbon nanotubes to construct CNT@IL structure, and the ionized film was irradiated and crosslinked with 150kGy. The three-dimensional network was dense and the interface was firmly anchored, with excellent comprehensive performance, hysteresis of 5%, creep of 6% at 1MPa, and full drift of 5% after 1000 cycles.

[0095] Compared with Example 1, Example 2 increased the crosslinking agent content to 0.3 parts and reduced the irradiation dose to 100 kGy. The crosslinking degree of PVDF and PVDF-HFP decreased, the gel content decreased to 58%, and the overall performance decreased. Hysteresis, creep and full drift all increased to 7%, but were still at a low level, proving that good network stability can still be maintained with an appropriate amount of crosslinking agent at a low irradiation dose.

[0096] Compared with Example 1, Example 3 increased the nano alumina content from 3 parts to 5 parts, maintained the gel content at 63%, and still showed good creep performance at 1MPa and full drift performance at 1000 cycles, at 6% and 8% respectively, indicating that high alumina content can effectively improve the rigidity and creep resistance of the film; however, due to the increase in rigid inorganic filler, the flexibility of the film was somewhat limited, resulting in a hysteresis performance increase to 8%.

[0097] Compared with Example 1, Example 4 uses TMPTA instead of TAIC as a crosslinking agent, and the gel content reaches 62%. The hysteresis, creep and full drift data are 5.5%, 6.5% and 5.5% respectively, which are very close to those of Example 1. This fully verifies the equivalence and universality of multifunctional acrylate crosslinking agents in capturing polymer free radicals and constructing three-dimensional networks.

[0098] Compared with Example 1, Comparative Example 1 did not add carbon nanotubes. Although it underwent irradiation crosslinking and the gel content reached 63%, due to the lack of interface anchoring and conductive network synergy of the CNT@IL structure, the ionic liquid was prone to migration and precipitation under long-term stress. This resulted in a significant deterioration of the 1MPa creep and 1000 full drift performance to 15%, an increase in hysteresis to 12%, and a significant decrease in sensor pressure sensitivity and signal fidelity.

[0099] Compared with Example 1, Comparative Example 2 only added a crosslinking agent but did not undergo high-energy irradiation treatment. The crosslinking agent only played a plasticizing role in the system and failed to form a three-dimensional crosslinking network. The gel content was 0, which could not effectively restrict the movement and slippage of molecular chains. The rigidity and elasticity of the film deteriorated, with a hysteresis of up to 20%. The creep at 1MPa and the full drift at 1000 cycles both deteriorated to 25%, which completely failed to meet the sensing requirements of low drift and high stability.

[0100] The technical effects of the present invention will be further explained below with reference to specific experimental results and accompanying drawings.

[0101] Figure 1 The Fourier transform infrared spectrum characterization of the ionogel film provided in Embodiment 1 of the present invention is shown in the figure. At 701 cm⁻¹... -1 and 740 cm -1 The characteristic peak of SNS symmetric stretching vibration appeared at 1332 cm⁻¹. -1 and 1350 cm -1 The characteristic peak of -SO2 asymmetric contraction vibration appeared at 1570 cm⁻¹. -1 The characteristic peak of imidazole ring skeletal stretching vibration appeared at 761 cm⁻¹, confirming the successful introduction of ionic liquid into the composite thin film system and the integrity of the molecular structure. Meanwhile, at 761 cm⁻¹... -1 794 to 796 cm -1 and 853 cm -1 The characteristic peaks corresponding to the α phase of polyvinylidene fluoride are significantly weakened at 840 cm⁻¹, while the characteristic peaks representing the β phase are at 840 cm⁻¹. -1 Significant enhancement in the vicinity, and with ionic liquids at 837 cm⁻¹ -1 The characteristic peaks at this location overlap and work together to form the 838 cm⁻¹ peak. -1 The characteristic peak at the location. This spectroscopic evidence indicates that high-energy irradiation crosslinking treatment successfully induced the transformation of polyvinylidene fluoride from the nonpolar α phase to the highly polar β phase, significantly enhancing the dipole moment and polar interaction within the material, optimizing the dielectric properties of the system, and reducing interfacial leakage current.

[0102] Figure 2 The images show the scanning electron microscope (SEM) morphology of the ion gel film provided in Example 1 of this invention at different magnifications. As shown, due to the gradient evaporation effect of the high-boiling-point solvent and the low-boiling-point solvent in the dual-solvent system, as well as the co-crystallization effect of polyvinylidene fluoride (PVDF) and PVDF-hexafluoropropylene copolymer, a morphology with micro / nano protrusions and porous structures is formed on the film surface. At the 20 μm and 5 μm scales, uniformly distributed micro / nano protrusion structures can be observed on the surface. Further local magnification at the 1 μm and 500 nm scales reveals a uniform linear rough folded vein structure on the protrusion surface. This micromorphology indicates that the non-covalently modified carbon nanotube and ionic liquid composite structure achieves uniform dispersion and low agglomeration effect in the film system. The ionic liquid acts as an interfacial bridger, confining the carbon nanotubes within the polymer matrix, which helps to achieve a structurally stable sensing layer. Simultaneously, the micro / nano protrusions and porous structure on the surface provide compressible volume when the sensor is under pressure, significantly increasing the effective contact area change rate between the sensitive layer and the electrode, thus endowing the film with excellent sensing sensitivity.

[0103] Figure 3 The figure shows the hysteresis performance test curves of the pressure sensor fabricated from the ionogel film provided in Example 1 of this invention. As shown, during the step-by-step pressurization and depressurization process, the loading curve and unloading curve highly overlap, and the area enclosed by the hysteresis loop is small. This indicates that the sensor exhibits extremely low mechanical hysteresis error during deformation and recovery under stress, and can quickly recover to its initial state after unloading, with no obvious residual plastic deformation. These test results confirm that the three-dimensional irradiated crosslinking network and non-covalent interface coupling mechanism constructed in this invention can effectively restrict the slippage of polymer molecular chains, endowing the film with excellent high resilience and low hysteresis characteristics.

[0104] Figure 4 The figure shows the 1MPa creep performance test curve of the pressure sensor made from the ionogel film provided in Example 1 of this invention. As shown in the figure, during the test period of applying a constant pressure of 1MPa and maintaining it for 1 hour, the sensor output signal quickly reaches a stable plateau, and the signal fluctuation is minimal throughout the pressure holding phase, with no obvious creep drift phenomenon that decays over time. This result demonstrates the confinement effect of the three-dimensional cross-linked network on molecular chain slippage, and the effective physical confinement effect of the non-covalent modified structure on the ionic liquid, enabling the film to maintain excellent dimensional stability under long-term static load, overcoming the technical defect of traditional ionogel films being prone to creep.

[0105] Figure 5 The figure shows the full-scale dynamic drift test curves of the pressure sensor fabricated from the ionogel film provided in Embodiment 1 of this invention after 1000 cycles. As shown, during 1000 consecutive rapid cyclic loading cycles from zero pressure to the expected range and back to zero pressure, the sensor's full-scale output signal remained highly consistent, with extremely high overlap of the cyclic curves. This result conclusively demonstrates that the ionogel film provided by this invention possesses excellent cyclic reliability and anti-signal drift capability under long-term high-frequency dynamic loads. The three-dimensional cross-linked network cuts off the ion leakage channels formed by the propagation of microcracks in the matrix, effectively preventing ion leakage caused by micro-defects, and meeting the application requirements for accurate and stable pressure feedback in complex working environments.

[0106] Figure 6 and Figure 7These are front and top views of the pressure sensor fabricated from the ion gel film provided in Embodiment 1 of the present invention. As shown, the pressure sensor adopts an asymmetric stacked structure, comprising, from top to bottom, a backing substrate, an ion gel film, and interdigitated electrodes. The backing substrate serves as the bottom support, providing macroscopic mechanical support and dimensional stability for the internal sensitive layer; the interdigitated electrodes are disposed below the ion gel film, and their alternating finger-like structures create a symmetrical edge electric field; the ion gel film forms a stable double-layer capacitor structure under the action of the electric field. The tight adhesion between the backing substrate and the ion gel film eliminates interface voids, avoiding additional parasitic capacitance introduced by the interface air layer, and ensuring high fidelity and long-term reliability of the sensor's capacitive signal.

[0107] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A low-drift, highly stable ionogel film, characterized in that, The raw materials for preparation, by weight, include: 15-30 parts of polyvinylidene fluoride polymer, 10-20 parts of ionic liquid, 0.1-0.6 parts of carbon nanotubes, 0.1-5 parts of nanofiller, 0.1-0.6 parts of crosslinking agent, and 55-70 parts of solvent; The carbon nanotubes are coated with the ionic liquid to form a non-covalently modified CNT@IL structure; the polyvinylidene fluoride polymer is cross-linked by radiation through the cross-linking agent to form a three-dimensional cross-linked network structure. In the infrared spectrum of the ionogel film, 760~800 cm⁻¹ -1 The intensity of the characteristic peak of the α-crystal form of polyvinylidene fluoride at that location is below 830–850 cm⁻¹. -1 The intensity of the characteristic peak of the β-crystal form of polyvinylidene fluoride at that location.

2. The ionogel film according to claim 1, characterized in that, Based on the total mass of the polyvinylidene fluoride polymer, the PVDF content in the polyvinylidene fluoride polymer is 80%~95%, and the PVDF-HFP content is 5%~20%; The PVDF has a weight-average molecular weight of 900,000 to 1,100,000 and a molecular weight distribution of 1.8 to 2.

2. The weight-average molecular weight of the PVDF-HFP is 300,000 to 500,000, and the molecular weight distribution is 1.9 to 2.

3.

3. The ionogel film according to claim 1, characterized in that, The ionic liquid is selected from at least one of 1-ethyl-3-methylimidazolium trifluoromethanesulfonylimide, 1-butyl-3-methylimidazolium di(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, 3-methyl-1-hexylimidazolium bromide, and 1-ethyl-3-methylimidazolium acetate. The nanofiller is selected from at least one of α-alumina or γ-alumina; The crosslinking agent is selected from at least one of triallyl isocyanurate, triallyl cyanurate, or trimethylolpropane triacrylate.

4. The ionogel film according to claim 1, characterized in that, The solvent includes a first solvent and a second solvent; the first solvent is N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone, accounting for 80% to 95% of the total mass of the solvent; the second solvent is dimethyl carbonate, accounting for 5% to 20% of the total mass of the solvent.

5. The ionogel film according to claim 1, characterized in that, The infrared spectrum of the ionogel film also includes the 701-705 cm⁻¹ range. -1 and 738~742 cm -1 The characteristic peak of SNS symmetric stretching vibration at 1330~1335 cm⁻¹ -1 and 1348~1352 cm -1 The characteristic peak of the -SO2 asymmetric contraction vibration at 1568~1572 cm⁻¹, and the characteristic peak of the -SO₂ contraction vibration at 1568~1572 cm⁻¹. -1 The characteristic peak of the stretching vibration of the imidazole ring skeleton at that location.

6. A method for preparing an ionogel thin film as described in any one of claims 1 to 5, characterized in that, Includes the following steps: Step S1: Add carbon nanotubes to a solvent, disperse them by ultrasonication, add ionic liquid and nanofiller, continue ultrasonication and mechanical stirring, so that the ionic liquid coats the surface of carbon nanotubes through non-covalent interaction to obtain CNT@IL dispersion. Step S2: Add the polyvinylidene fluoride polymer and crosslinking agent to the CNT@IL dispersion, heat and stir until completely dissolved to obtain an ionized solution; Step S3: Coat the ionized solution onto the substrate, heat to evaporate the solvent and dry to form a film, and then bake under vacuum to obtain a nascent ion gel film; Step S4: Under inert gas protection, the nascent ionogel film is subjected to high-energy irradiation treatment with an irradiation dose of 50~200kGy, an irradiation rate of 1~3 m / min, an irradiation distance of 10~20cm, and a nitrogen irradiation environment. Multiple irradiations with small doses are used, followed by annealing treatment to obtain the ionogel film.

7. The method for preparing an ionogel film according to claim 6, characterized in that, In step S1, the ultrasonic dispersion time is 30-60 min, the ultrasonication time is 10-30 min, and the mechanical stirring conditions are stirring at 30-50℃ for 2-4 h. In step S2, the polyvinylidene fluoride polymer includes PVDF and PVDF-HFP, and the heating and stirring conditions are stirring at 50~60℃ for 12~24h.

8. The method for preparing an ionogel film according to claim 6, characterized in that, In step S3, the thickness of the wet film formed by coating is 100~2000μm; the conditions for drying the film by heating and evaporating the solvent are 70~85℃ for 20~26h; the conditions for vacuum baking are 70~80℃ for 46~50h. In step S4, the irradiation source for the high-energy irradiation treatment is an electron beam or gamma rays; the annealing treatment is performed at 90~110℃ for 1~2 hours.

9. A pressure sensor, characterized in that, It includes a backing substrate, an ion gel film as described in any one of claims 1 to 5, and interdigitated electrodes arranged in sequence.

10. The application of the pressure sensor as described in claim 9 in flexible electronic skin, wearable medical devices, human-computer interaction, or soft robots.